2012
DOI: 10.1080/20445911.2011.613819
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of emotional pictures: Behavioural and electrophysiological measures

Abstract: The effects of emotional content of images on recognition memory were studied, bringing together electrophysiological (Event-Related brain Potentials, ERPs) and behavioural (accuracy and speed of recognition, and remember/know judgements) indices. In the study phase, participants assessed 120 images on the scales of valence and arousal. In the test phase, ERPs were recorded while participants viewed again the images, put together with 120 new, and were asked to make old/new decisions and remember/know judgemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 115 publications
2
5
0
Order By: Relevance
“…The absence of an LPC old/new effect for fearful faces at the group level in both studies was due to a positivity for fearful new compared to neutral new faces. Even though the LPC old/new effect was larger for emotional than neutral words, pictures, faces (and negative words, pictures, and faces in particular) in multiple previous studies (Dietrich et al, 2001;Inaba et al, 2005;Johansson et al, 2004;Langeslag and Van Strien, 2008;Pérez-Mata et al, 2012;Weymar et al, 2009), several other previous studies have observed a reduced or even inversed LPC old/new effect for emotional compared to neutral words or pictures because of a positivity for new emotional compared to new neutral stimuli (Langeslag and Van Strien, 2008;Maratos et al, 2000;Van Strien et al, 2009). The current study now demonstrates a similar effect for fearful faces.…”
Section: Tablesupporting
confidence: 56%
See 1 more Smart Citation
“…The absence of an LPC old/new effect for fearful faces at the group level in both studies was due to a positivity for fearful new compared to neutral new faces. Even though the LPC old/new effect was larger for emotional than neutral words, pictures, faces (and negative words, pictures, and faces in particular) in multiple previous studies (Dietrich et al, 2001;Inaba et al, 2005;Johansson et al, 2004;Langeslag and Van Strien, 2008;Pérez-Mata et al, 2012;Weymar et al, 2009), several other previous studies have observed a reduced or even inversed LPC old/new effect for emotional compared to neutral words or pictures because of a positivity for new emotional compared to new neutral stimuli (Langeslag and Van Strien, 2008;Maratos et al, 2000;Van Strien et al, 2009). The current study now demonstrates a similar effect for fearful faces.…”
Section: Tablesupporting
confidence: 56%
“…This LPC old/new effect is thought to reflect the recollection process (Curran and Clearly, 2003;Van Strien et al, 2005;Weymar et al, 2009). In line with the notion that emotion boosts recollection more than familiarity (Ochsner, 2000), the emotional modulation of the LPC old/new effect is more consistently observed across studies (Dietrich et al, 2001;Inaba et al, 2005;Langeslag and Van Strien, 2008;Pérez-Mata et al, 2012;Weymar et al, 2009) than the emotional modulation of the N400 old/new effect. For example, the LPC old/new effect was larger for negative than positive and neutral faces (Johansson et al, 2004).…”
Section: Introductionsupporting
confidence: 56%
“…Our first component of interest, the LPC, is a positive ERP modulation maximal over medial posterior recording sites, with a tendency to be more focused over the left hemisphere (Friedman & Johnson, 2000), around 400 to 800 ms post-stimulus which has been associated with the recollection of accurate source information from both a threshold (Rugg, Schloerscheidt, Doyle, Cox, & Patching, 1996;Rugg, Schloerscheidt, & Mark, 1998;Vilberg, Moosavi, & Rugg, 2006;Wilding, Doyle, & Rugg, 1995;Wilding & Rugg, 1996) and graded perspective (Leynes & Phillips, 2008 (Woodruff, Hayama, & Rugg, 2006). In line with its proposed role in memory related processing, the episodic memory related LPC has been associated with activity in the left medial temporal (Duzel et al, 2001) and parietal regions (Caplan, Glaholt, & McIntosh, 2009;Pérez-Mata, López-Martín, Albert, Carretié, & Tapia, 2012).…”
Section: Neurobiology Of Learning and Memorymentioning
confidence: 79%
“…For the FER phase, to improve the responses' signal-to-noise ratio (avoiding responses biased by attentional distraction or technical problems in the recordings), we removed trials with RTs > 2500 ms ( Pérez-Mata et al, 2012 ; Hatzidaki et al, 2015 ; Pelaez et al, 2016 ) and then also excluded those that fell 3 SDs away from the mean of each subjects' RT. Also, to exclude data that may not reflect our target psychological processes in both phases of the task, we discarded subjects whose mean RTs fell 3 SDs from the sample's mean in each condition ( de la Fuente et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%